Nonylphenol Impairs Steroidogenesis And Lipid Homeostasis During Testicular Development In Mouse Organ Culture - Tajes Ardanaz, Oliverio Julián (2024)
Nonylphenol (NP), a chemical known for its endocrine-disrupting properties, is an environmental pollutant associated with numerous adverse effects on male fertility in both animal models and wild species. In this study, we used a gas-liquid interface testicular culture system to investigate the impact of NP on ex vivo neonatal testicular development. Our objectives were to measure the production levels of testosterone (Tes) and 17β-estradiol (E2), to analyze the expression of genes encoding key proteins involved in the biosynthesis of these hormones, and to assess alterations in testicular lipid composition in NP-exposed ex vivo cultured testes. Our results demonstrated that NP disrupted both the differentiation and maintenance of spermatogenic cells. Furthermore, NP significantly downregulated the transcript levels of marker genes associated with spermatogonial, meiotic, and haploid spermatogenic cells compared to controls. Histological analysis revealed that the seminiferous tubules were depleted of spermatogenic cells, with a concomitant increase in the number of interstitial cells. These observations were consistent with the macroscopic finding that, after 22 days of culture, the tissue size was significantly reduced compared to the control. Notably, NP-exposed tissue produced higher levels of Tes compared to the control during the 0 to 25-day culture period, while E2 levels tended to decrease. This was consistent with an observed increase in the expression of 3β-Hydroxysteroid Dehydrogenase (3β- Hsd1) and a decrease in Cytochrome P450 Aromatase (Cyp19a1), enzymes involved in the production of Tes and E2, respectively. In addition, the explants exposed to NP had higher levels of neutral lipids, particularly triacylglycerols (TAG) and cholesterol esters (CE), compared to those cultured under control conditions. We observed an increase in neutral lipid droplets within both intratubular and interstitial cells, likely containing the accumulated TAG and CE. In summary, this study shows that NP negatively impacts prepubertal spermatogenesis and germ cell maintenance, while also disrupting steroidogenesis and causing imbalances in hormonal and lipid homeostasis.